Topical blood products modulate the effects of ophthalmic antibiotics against common bacterial pathogens in dogs with infectious keratitis - Kubai, Melissa A.; Roy, Mackenzie M.; Stinman, Chloe C.; Kenne, Danielle E.; Allbaugh, Rachel A.; Sebbag, Lionel (Frontiers in Veterinary Science, 2024)
Bacterial keratitis is a common and serious condition that often leads to vision impairment and potential loss of the eye if not treated promptly and adequately. Topical blood products are often used concurrently with topical antibiotics, helping to mitigate corneal 'melt' from proteases released on to the ocular surface. However, blood products are rich in albumin and could affect the efficacy of antibiotics due to drug-protein binding. In this study, serum and plasma samples were harvested from 10 healthy dogs and 10 healthy horses, obtaining fresh and frozen (1 month at -20°C) aliquots for in vitro experiments. Albumin levels were quantified using species-specific ELISA kits. Thirty bacteria (10 Staphylococcus pseudintermedius, 10 Streptococcus canis, 10 Pseudomonas aeruginosa), isolated from canine patients with infectious keratitis, were each tested with blank plates as well as commercial susceptibility plates (Sensititre™ JOEYE2) to assess the minimal inhibitory concentration (MIC) of 17 different antibiotics in the absence (control) or presence of eight test groups: serum or plasma (fresh or frozen) from canines or equines. Albumin concentrations ranged from 13.8-14.6 mg/ml and 25.9-26.5 mg/ml in canine and equine blood products, respectively. A direct antimicrobial effect was observed mostly with equine vs. canine blood products (specifically serum and to a lesser degree plasma), and mostly for Staphylococcus pseudintermedius isolates. MICs generally increased in the presence of blood products (up to 10.8-fold), although MICs also decreased (down to 0.25-fold) for selected antibiotics and ocular pathogens. Median (range) fold changes in MICs were significantly greater (P=0.004) with the canine blood products [2(0.67-8.1)] than the equine blood products [2(0.5-5)]. In practice, clinicians should consider equine over canine blood products (lesser impact on antimicrobial susceptibility), serum over plasma (greater antimicrobial effects), and administering the blood product ≥15min following the last antibiotic eyedrop to minimize the amount of albumin-antibiotic binding in tear film.